Measuring Adaptive Team Coordination in an Enroute Care Training Scenario. (September 2022) - Grimm, David A.P.; Gorman, Jamie C.; Robinson, Eric; Winner, Jennifer
Teams must adapt and coordinate in high-stress environments in response to challenging situations. Communication is vital to coordination and can provide insights into effective team adaptation. We analyzed communication speaker data, consisting of a physician, nurse, and respiratory therapist, from a critical care simulation. We analyzed speaker flow data and quantified continuous reorganization of team communication states using entropy, which measures variety, and determinism, which measures repeatability of patterns. Using Ashby's law of requisite variety, we hypothesized that higher performance would be correlated with greater variety: higher entropy and lower determinism. We further hypothesized that relationships would be stronger during times containing perturbations than during times without perturbations. Results supported the first hypothesis, effectiveness was correlated with greater communication variety. The correlation was numerically larger for perturbation segments, but the difference from non-perturbation segments was not statistically significant. We discuss potential applications and implications for dynamic measures of team effectiveness.